HUBUNGAN KARAKTERISTIK RUMAH DENGAN KEJADIAN ISPA PADA BALITA DALAM KELUARGA PEROKOK DI KELURAHAN GUNDALING I KECAMATAN BERASTAGI KABUPATEN KARO TAHUN 2014 - Raja Nindangi Lingga; nurmaini *; devi nuraini santi (Lingkungan dan Kesehatan Kerja, 2014)
Acute Respiratory Infections (ARIs) is a major cause of morbidity and mortality in communicable disease in world especially for children under 5 years old. Children under 5 years old is vulnerable in Acute Respiratory Infections (ARIs). The major risk  of Acute Respiratory Infections (ARIs) are bad house physical conditions, and smoking habits. The ciggarets smoke contains tar which is affects the respiratory system of children under 5 years old and give a high risk for the accidens of Acute Respiratory Infections (ARIs). The purpose of this research is to find out the correlation between house’s characteristics ( residential density, ventilation, floor, ceiling, wall, lighting, temperature, and humidity) with Acute Respiratory Infections (ARIs) cases of  children under 5 years old which is live in the  smoking habits families in Kelurahan Gundaling I. This is a descriptive-analytic with case control design research. The samples of this researh is 62 children under 5 years old who lives in Kelurahan Gundaling I which is consist of 31 samples total sampling for case who is the sufferer of Acute Respiratory Infections (ARIs) which is recorded on the medical record of public health centre in Berastagi and 31 children under 5 years old for control who live around Acute Respiratory Infections (ARIs) sufferer. Data was analyzed by Chi Square with 95% confidence interval. The research shows there is no correlation between house’s characteristics with Acute Respiratory Infections (ARIs) cases in children under 5 years old. Smoking habits near children under 5 years old has a significant correlation with Acute Respiratory Infections (ARIs) cases in children under 5 years old (p<0,05). As suggestions for people who live in Kelurahan Gundaling I it is required to not smoke around children under 5 years old and to not smoke in home. It is required for a prevention through counseling by health officer about the effect and hazard of cigarette for passive smoker.